Interview with Prof. Karin de Boer - de Boer, Karin; Ranaee, Mahdi (Con-Textos Kantianos. International Journal of Philosophy, 2025)
In this interview, conducted by Mahdi Ranaee, Professor Karin de Boer discusses key aspects of her research in Kantian philosophy, with a particular focus on the Critique of Pure Reason and its historical context. She reflects on the interpretive challenges posed by Kant’s texts, the influence of German Idealism, and her methodological approach to philosophical scholarship. The conversation also touches on the contemporary relevance of Kant’s thought and the importance of situating his work within broader philosophical traditions.